Law without nations - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Amherst series in law, jurisprudence, and social thought., 2011)
'Law without nations' examines the ways in which the growing internationalization of law affects domestic national law, the relationship between cosmopolitan legal ideas and understandings of national identity, and the intersections of identity and law based on the liberal tradition of jurisprudence.